Model Prophet dengan Random Search untuk Peramalan Jumlah Kunjungan Wisatawan Mancanegara - Gessya Saefani; Teti Sofia Yanti (Jurnal Riset Statistika, 2025)
Abstract. Time series analysis is used to identify patterns and forecast values based on temporal sequences. In the tourism sector, forecasting the number of international tourist arrivals to Bali is essential to support more strategic planning. This study utilizes the Prophet model, which is designed to handle both linear and non-linear trends, seasonal patterns, and the effects of holidays or special events. The data used consists of monthly international tourist arrivals to Bali from 2008 to 2024. The analytical process includes data exploration, descriptive analysis, Prophet modelling with various component combinations, model performance evaluation using MAPE, and selection of the best model. A total of six Prophet models were built, three of which were optimized using the random search method. The best-performing model (Model 6), which accounts for the impact of the COVID-19 lockdown, achieved a high level of accuracy with a MAPE of 7,60%. Excluding any external variables not included in the model, the 2025 forecast indicates an upward trend in tourist arrivals. All predicted values exceed the historical average (310.352) and surpass the previous peak (625.665), with the highest forecast in November 2025 reaching 676.293 visits. These findings reflect the potential for post-pandemic recovery and growth in Bali's tourism sector and can serve as a foundation for more targeted policy-making. Abstrak. Analisis deret waktu digunakan untuk mengidentifikasi pola dan meramalkan nilai berdasarkan urutan waktu. Dalam bidang pariwisata, peramalan kunjungan wisatawan mancanegara ke Bali penting untuk perencanaan strategis. Penelitian ini menggunakan model Prophet yang mampu menangani tren linear dan non-linear, pola musiman, serta pengaruh hari libur dan peristiwa khusus. Data yang digunakan berupa jumlah kunjungan wisatawan mancanegara ke Bali per bulan dari tahun 2008 hingga 2024. Tahapan analisis mencakup eksplorasi data, analisis deskriptif, pemodelan Prophet dengan berbagai variasi komponen, evaluasi performa model menggunakan MAPE, hingga pemilihan model terbaik. Sebanyak enam model Prophet dibangun, tiga di antaranya dioptimasi menggunakan metode random search. Model terbaik (Model 6) yang mempertimbangkan efek lockdown COVID-19 menghasilkan tingkat akurasi tinggi dengan MAPE sebesar 7,60%. Tanpa mempertimbangkan variabel eksternal yang tidak dilibatkan dalam model, hasil peramalan untuk tahun 2025 menunjukkan tren peningkatan kunjungan. Seluruh nilai ramalan melebihi rata-rata historis (310.352) dan bahkan melampaui rekor kunjungan sebelumnya (625.665), dengan puncak pada November 2025 sebesar 676.293 kunjungan. Temuan ini menunjukkan potensi pemulihan dan pertumbuhan pariwisata Bali pascapandemi serta dapat menjadi acuan bagi kebijakan yang lebih terarah.